Trabalhando pelo sucesso escolar: as vivências de uma professora em seu primeiro ano de atuação na escola pública. - Silveira, Maria de Fátima Lopes da (2002)
This work is orderly following this question: How to configure the professional learning of the teacher in the beginning of the carrier, in attempt to overcome the scholar failure of second grade students of the public elementary school? The research started beginning in 1999, during my first experience as teacher in the school in São Carlos-SP-Brazil. In this work, between the learning, is possible to detach: the attribution of the meanings to the theoretical references getting during the process of the fundamental development, and how to translate to the professional practice engaged with the scholar success; the construction of the teaching process related to the reading and writing (Ferreiro, 1995).